JOB SATISFACTION OF HIGH SCHOOL TEACHERS OF ASSAM - Kakati, Dr. Karabi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The present study was conducted to study the job satisfaction of High School teachers of Assam. The sample consisted of 500 High School teachers, which included male-female and urban-rural categories. Yudhvirendra Mudgil, Prof. I.S. Mhar, and Prabha Bhatia’s Teachers’ Job Satisfaction Scale (TJSS) was used to collect the data. The results indicated that there is a significant difference in job satisfaction of male and female High School teachers.